Exploration of Sorafenib Influences on Gene Expression of Hepatocellular Carcinoma - Wang, Huancheng; Liu, Jia (Frontiers in Genetics, 2020)
Purpose: To develop a comprehensive differential gene profile for hepatocellular carcinoma (HCC) patients treated with Sorafenib. Methods: The RNA sequencing data and miRNA sequencing data of 114 HCC patients treated with Sorafenib only and 326 HCC control patients treated without any chemotherapeutic drugs were studied using differential expression, functional enrichment and protein-protein interaction analysis. Results: Compared with HCC patients without any chemotherapy drugs, the Sorafenib treated patients develop 66 differentially expressed genes (DEGs), including 12 up-regulated genes and 54 down-regulated genes. Additionally, 3 miRNAs (DEMs) also show specific expression pattern. With further analysis, 5 primary genes including HTR2C, TRH, AGTR2, MCHR2 and SLC6A2 as well as 3 miRNAs (hsa-miR-4445, hsa-miR-466 and hsa-miR-2114) have been suggested as the potential targets for Sorafenib. The specific gene expression of 5 genes have been validated in clinical HCC patients by ELISA method. GO and KEGG functional enrichment analysis indicate several significantly enriched Biological Processes (BP) , Cellular Components (CC) as well as Molecular Functions (MF). Conclusion: Since Sorafenib is becoming increasingly important in HCC treatment clinically, this study will help us understand the potential targets and eliminate diverse existing side effects of it as well as explore several potential clinical biomarkers with comprehensive analysis of differential gene expression profile.